Finding the Holy Grail of Library Value: Characteristics of Academic Libraries at Universities with High Retention Rates - Szpunar, Ruth; Bradley, Eric (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – What are the characteristics of academic libraries at schools with high retention rates? To help libraries tell the story of their impact, we sought to determine which academic library practices were linked to high retention rates.Methods – The investigators created a survey for the United States Great Lakes region library deans and directors in the Spring of 2022 with 19 questions about their library services and staffing. The survey was sent to 226 schools and had a response rate of 31%. We compared the resulting information to publicly available data on student retention from ACRL Metrics and IPEDS to look for correlations and associations.Results – Statistical analysis used the Chi-squared test and the Pearson correlation to calculate association and correlation. This found six attributes of student connections with library staff and with unique local collections that were associated with statistically significant differences in retention rates and institutions. These attributes were institutions who: used students as archives student workers, used students to staff reference desks, conducted multiple library instruction sessions with the same class, had a staffed archive or special collection space, had an institutional repository that included student work, or had an Instagram account.Conclusion – The survey results gave a clear profile of academic libraries with above average retention, particularly in terms of student focused initiatives and the curation of unique collections. Additionally, the survey gave a foundation, with recommendations, for future researchers to build upon.